Lung stiffness of C57BL/6 versus BALB/c mice - Andrés Rojas-Ruiz; Magali Boucher; Rebecka Gill; Louis Gélinas; Fun-Qun Tom; Liah Fereydoonzad; Percival Graham; Jorge Soliz; Ynuk Bossé (Scientific Reports, 2023)
Abstract This study was undertaken to determine whether a smaller lung volume or a stiffer lung tissue accounts for the greater lung elastance of C57BL/6 than BALB/c mice. The mechanical properties of the respiratory system and lung volumes were measured with the flexiVent and compared between male C57BL/6 and BALB/c mice (n = 9). The size of the excised lung was also measured by volume liquid displacement. One lobe was then subjected to sinusoidal strains in vitro to directly assess the mechanical properties of the lung tissue, and another one was used to quantify the content of hydroxyproline. In vivo elastance was markedly greater in C57BL/6 than BALB/c mice based on 5 different readouts. For example, respiratory system elastance was 24.5 ± 1.7 vs. 21.5 ± 2.4 cmH2O/mL in C57BL/6 and BALB/c mice, respectively (p = 0.007). This was not due to a different lung volume measured by displaced liquid volume. On the isolated lobes, both elastance and the hydroxyproline content were significantly greater in C57BL/6 than BALB/c mice. These results suggest that the lung elastance of C57BL/6 mice is greater than BALB/c mice not because of a smaller lung volume but because of a stiffer lung tissue due to a greater content of collagen.